Role of drying technology in probiotic encapsulation and impact on food safety. Issue 8 (15th June 2022) - Sehrawat, Rachna; Abdullah, S.; Khatri, Prateek; Kumar, Lokesh; Kumar, Anit; Mujumdar, Arun Sadashiv
Abstract: The world's urban population is expected to double by 2050. Urbanization is changing food consumption patterns, and the global market is flooded with functional foods, specifically probiotics, for their gut health advantages. Awareness about the healthy human microbiome among the consumer has prompted them to demand probiotic foods. Due to their potential health benefits, probiotics have been incorporated into several dairy and nondairy products. To overcome the hurdles associated with the low viability of the beneficial microorganism, microencapsulation of probiotic bacteria and yeast is of immense importance. Microencapsulation enhances the viability of probiotics during different processing techniques and under gastrointestinal conditions. So, it is critical to control and design the drying process technology for probiotics encapsulation to achieve higher viability. The purpose of the review is to compile the commonly utilized drying technique for probiotics with their principle, advantages, and disadvantages, mechanism of inactivation, recent research, and cost involved in the processing.